Review and evolution of guidelines for diagnosis of COVID-19 vaccine induced thrombotic thrombocytopenia (VITT) - Favaloro, Emmanuel J; Pasalic, Leonardo; Lippi, Giuseppe (Clinical chemistry and laboratory medicine, 2022)
Coronavirus disease 2019 (COVID-19) is a life-threatening infectious disease caused by Severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2). In response to the still ongoing pandemic outbreak, a number of COVID-19 vaccines have been quickly developed and deployed. Although minor adverse events, either local (e.g., soreness, itch, redness) or systematic (fever, malaise, headache, etc.), are not uncommon following any COVID-19 vaccination, one rare vaccine-associated event can cause fatal consequences due to development of antibodies against platelet factor 4 (PF4), which trigger platelet activation, aggregation, and possible resultant thrombosis, often at unusual vascular sites. Termed thrombosis with thrombocytopenia syndrome (TTS) by reporting government agencies, the term vaccine-induced (immune) thrombotic thrombocytopenia (VITT) is more widely adopted by workers in the field. In response to increasing reports of VITT, several expert groups have formulated guidelines for diagnosis and/or management of VITT. Herein, we review some key guidelines related to diagnosis of VITT, and also provide some commentary on their development and evolution.